A comparative study of open and closed-air cycles for desalination system using the humidification–dehumidification method. Issue 11 (1st October 2021) - Mohamed, A. S. A.; Shahdy, Abanob G.; Ahmed, M. Salem
Abstract : Humidification dehumidification water desalination system using two cycles of air flow (open and closed-air cycles). Abstract : An experimental evaluation of a solar water desalination system with humidification–dehumidification technique has been conducted using two cycles of air flow (open and closed-air cycles). The performance of the proposed system was investigated at various operating parameters. The performance of the open-air cycle is compared with the closed-air cycle. In addition, an economic analysis for the cost of producing one liter of fresh water was performed. The results indicated that the desalination system gives maximum values at the water temperature of 70 °C for the productivity of fresh water, GOR, and the fresh water cost per liter, which is about 4.98 L h −1, 0.53, and 0.015 for the open-air cycle, while it gives about 6.16 L h −1, 0.84, and 0.012 for the closed-air cycle. The results show that the system productivity, GOR, and recovery ratio in the closed-air cycle is higher than that in the open-air cycle by about 74%, 193%, and 27% at the water temperature of 50 °C and water flow rate of 4.05 kg min −1, respectively. The humidifier and dehumidifier efficiency in the closed-air cycle is less than that in the open-air cycle. The results also show that the energy consumed in the open-air cycle is almost twice that in the closed-air one. Finally, the cost of fresh water produced per one liter in the closed-air cycle is less than that in the open-air cycle by 20%.